PENGGUNAAN METODE HOT FIT DALAM EVALUASI KEBERHASILAN IMPLEMENTASI SISTEM INFORMASI: STUDI KASUS SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) ON LINE KOTA YOGYAKARTA UNTUK JENJANG SMP - , ASEP SUBAGIYO, Dr. Ir. Eko Nugroho, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Evaluation of PPDB On Line Information System is crucial to ensure its effective implementaion and positive impact on education public services of Kota Yogyakarta government, espcesially new students acceptance process. HOT-Fit framework is used for the evaluation, to find out the concept of fit between human, organization and technology. Evaluation based on user perception, by using research samples as many as 34 respondents. The instrument is the questionaire which scaled by likert. As data analysis method, used Structural Equation Model or SEM and as executed by software SmartPLS. The result with Î± = 0.10 indicates that system use is significantly influenced by the quality system, quality service, and user satisfaction. User satisfaction is significantly influenced by the quality of service. While net benefits are significantly influenced by user satisfaction, structure and environtment of organization. Relationships H-O-T component is generated as follows: H-O Relations is not real, and very weak, H-T relationship is real and strong enough, and O-T relationship is real and very weak.